A Study of WSN Based Application Using RFID - Keerthana, J.P; Selvi, R. Chithirai (International Journal of Computer Sciences and Engineering, 2025)
WSN, which aims to exchange data wirelessly in a short distance using short-wavelength radio transmissions, is providing a necessary technology to create convenience, intelligence and controllability. Using RIFD technique to sense and monitoring the environment. Integrating RIFD with WSN not only provides identity and location of an object but also provides the information regarding the condition of the object carrying the sensors enabled RIFD tag. This paper discuss about the RIFD technology, which are used by the WSN through Zigbee device such as in Agriculture, Home Appliances and Health Care Monitoring. These applications are used for managing the user’s time and cost and also reduced human resources and improve productivity.